Adivasis and the state :subalternity and citizenship in India's Bhil heartland - Nilsen, Alf Gunvald (South Asia in the social sciences, 2018)
"In Adivasis and the State, Alf Gunvald Nilsen presents a major study of how subalternity is both constituted and contested through state-society relations in the Bhil heartland of western India. The book unravels the historical processes that subordinated Bhil Adivasi communities to the everyday tyranny of the state and investigates how social movements have mobilised to reclaim citizenship. In doing so, the book also reveals how collective action from below transform the meanings of governmental categories, legal frameworks, and universalising vocabularies of democracy. At the core of the book lies a concern with understanding the dialectics of power and resistance that give form and direction to the political economy of democracy and development in contemporary India. Towards this end, Adivasis and the State contributes a sustained and nuanced Gramscian analysis of hegemony in order to interrogate the possibilities and limits of subaltern political engagement with state structures"--